In situ hybridization of carbon nanotubes with bacterial cellulose for three-dimensional hybrid bioscaffolds. (July 2015) - Park, Subeom; Park, Jooyeon; Jo, Insu; Cho, Sung-Pyo; Sung, Dongchul; Ryu, Seungmi; Park, Minsung; Min, Kyung-Ah; Kim, Jangho; Hong, Suklyun; Hong, Byung Hee; Kim, Byung-Soo
Abstract: Carbon nanotubes (CNTs) have shown great potential in biomedical fields. However, in vivo applications of CNTs for regenerative medicine have been hampered by difficulties associated with the fabrication of three-dimensional (3D) scaffolds of CNTs due to CNTs' nano-scale nature. In this study, we devised a new method for biosynthesis of CNT-based 3D scaffold by in situ hybridizing CNTs with bacterial cellulose (BC), which has a structure ideal for tissue-engineering scaffolds. This was achieved simply by culturing Gluconacetobacter xylinus, BC-synthesizing bacteria, in medium containing CNTs. However, pristine CNTs aggregated in medium, which hampers homogeneous hybridization of CNTs with BC scaffolds, and the binding energy between hydrophobic pristine CNTs and hydrophilic BC was too small for the hybridization to occur. To overcome these problems, an amphiphilic comb-like polymer (APCLP) was adsorbed on CNTs. Unlike CNT-coated BC scaffolds (CNT-BC-Imm) formed by immersing 3D BC scaffolds in CNT solution, the APCLP-adsorbed CNT-BC hybrid scaffold (CNT-BC-Syn) showed homogeneously distributed CNTs throughout the 3D microporous structure of BC. Importantly, in contrast to CNT-BC-Imm scaffolds, CNT-BC-Syn scaffolds showed excellent osteoconductivity and osteoinductivity that led to high bone regeneration efficacy. This strategy may open a new avenue for development of 3D biofunctional scaffolds for regenerative medicine.